ANALISIS YURIDIS TERHADAP PUTUSAN LEPAS PADA TINDAK PIDANA KORUPSI DALAM PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1555K/PID.SUS/2019 - Sunny Shilby (Jurnal Hukum Adigama, 2021)
Indonesia is a country of law. One of the fields of law is criminal law. Actions that are contrary to the law are called criminal offenses. One of the criminal offenses that has always been in the spotlight is corruption. Corruption is considered as an action that endangers the state's efforts to achieve their goals. This is the basis for the Indonesian state to make regulations regarding the Eradication of Corruption. This Constitution becomes the nation’s hope in eradicating corruption, however, the application of this Constitution in corruption that has clearly met its elements is frequently mismatches. One of the Constitution applications that is mismatches in corruption eradication is when dropping off the verdict to the Supreme Court of the Republic of Indonesia’s decision Number 1555 K/Pid.Sus/2019. How is the juridical analysis towards the verdict on corruption in the Supreme Court of the Republic of Indonesia’s decision Number 1555 K/Pid.Sus/2019? The author investigates this problem using normative legal research methods. The research data shows that the decision of the Supreme Court that releases the verdict to the defendant was not legally correct. It is better if the Corruption Eradication Commission follows the civil lawsuit procedure as regulated in Article 32 of Law Number 31 of 1999 concerning Eradication of Corruption in conjunction with Law Number 20 of 2011 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption as an effort to return the state losses due to the case.